La responsabilidad civil de las entidades de certificación en Colombia (2018)
The certification bodies created by Law 527 of 1999 carry out various activities, such as, among others, issuing certificates related to electronic or digital signatures for natural or legal persons and issuing certificates on verification regarding alteration between sending and receiving the data message and transferable electronic documents; these activities must be fully complied by the certification bodies, otherwise, the rights of subscribers will be affected. Under the civil liability regime, the certification bodies are obliged to respond for all damages caused in the performance of their duties, for the damages they may cause to subscribers, and to third parties in good faith.